Integrating Green Infrastructure into Urban Planning: Developing Melbourne’s Green Factor Tool - Bush, Judy (2021)
As cities increase in size and density, the ecosystem services supplied by urban greenery and green infrastructure are increasingly vital for sustainable, liveable urban areas. However, retaining and maximising urban greenery in densifying cities is challenging. Governments have critical roles in addressing these challenges through policy development and implementation. While there has been significant attention on the quality and quantity of green space on public land, there is an increasing focus on policy mechanisms for integrating green infrastructure into the private realm, including green roofs, walls, facades, balconies and gardens. As part of City of Melbourne’s efforts to increase greening across the municipality, its 2017 Green Our City Strategic Action Plan includes specific focus on the private realm, and development of regulatory processes for green infrastructure. This article reports on a participatory research project to develop a Green Factor Tool for application to building development proposals in Melbourne. We focus on the transdisciplinary collaborations that brought together contributions from researchers, practitioners, policymakers and designers. We discuss how local research on green space contributions to provision of ecosystem services shaped the design of the tool and provided the tool’s rigorous evidence-base. Finally, we consider the roles of urban planning in retaining and maximising urban green spaces in densifying urban areas.